A crise na sociedade do trabalho e sua importância na contextualização dos conteúdos curriculares do ensino médio - Torres, Julio Cesar [UNESP]; David, Alessandra; Lopes, Silvana Fernandes [UNESP] (My University, 2010)
This article has as objective to discuss some topics concerning the supposed crisis of the society of the work and its consequences for the debate in social sciences and also for the work category contextualization in the secondary school curriculum. As the work has represented an important explanation category for the classic social thought, the contemporary paradigm of deep metamorphoses in the world of the work and the advent of the new question (CASTELS, 1995; ROSANVALLON, 1995) backward the necessity to rethink the theoretical shades that base the interpretation of the social life on the current context, when the center position of the work is being questioned. Having taken some theoretical references from the sociology of the work, we search to delineate on a brief way the quarrel about the dimensions of the social and political phenomena these days and the importance of this debate on the contextualization of the secondary school curriculum contents.

O artigo tem como objetivo apresentar algumas considerações acerca da suposta crise da sociedade do trabalho e suas conseqüências tanto para o debate nas ciências sociais, como também para a contextualização da categoria trabalho no currículo do ensino médio. Tendo em vista o fato de o trabalho representar para o pensamento social clássico um referencial importante para a explicação dos fenômenos sociais, o paradigma contemporâneo de profundas metamorfoses no mundo do trabalho e o advento da nova questão social (CASTELS, 1995; ROSANVALLON, 1995) trazem a necessidade de repensarmos as matrizes teóricas que fundamentam algumas interpretações da vida social no contexto atual, quando a centralidade do trabalho vem sendo questionada. À luz de alguns referenciais teóricos da sociologia do trabalho, buscamos delinear sob a forma de um ensaio a discussão sobre as dimensões do social e do político na contemporaneidade e a importância desse debate na contextualização dos conteúdos curriculares do ensino médio brasileiro.
The crisis in the society of the work and its importance on the contextualization of the secondary school curriculum contents
Keywords: crise da sociedade do trabalho; educação e trabalho; contextualização dos conteúdos curriculares do ensino médio; society of the work; education and work; contextualization of secondary school curriculum contents